Dampak Brand Ambassador Shani Amelia terhadap Brand Awareness Yuba Tea - Christy, Silvia; Aulia, Sisca (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
This research was conducted with the aim of knowing the influence of brand ambassador Shani Amelia on Yuba Tea's brand awareness. The research was conducted using a quantitative approach with survey research methods. In order to get the research results, the researcher conducted a method by distributing questionnaires to 100 respondents using the Slovin Formula and the data collection technique used a purposive or judgmental sampling technique. The population was obtained from Yuba Tea's Instagram followers, which totaled 49,300, while the sample used had the criteria of respondents knowing Shani Amelia and Yuba Tea, aged 17-34 years, male and female, domicile in DKI Jakarta area spread from West Jakarta, South Jakarta, North Jakarta, East Jakarta, and Central Jakarta. This study uses the theory of brand ambassadors and brand awareness. Processing techniques and data analysis obtained from the correlation coefficient, coefficient of determination, normality test, partial test (t test), and simple linear regression analysis. The results of the correlation test were obtained with a value of 0.557 so that it could be concluded that the brand ambassador variable and brand awareness variable had a moderate correlation, so that it could be concluded that brand ambassador Shani Amelia had an influence on Yuba Tea's brand awareness. For the results of the coefficient of determination, the R value is 0.557, which means that the independent variable (x) brand ambassador has an influence on the engagement variable (y) brand awareness because it approaches one. From the data that has been obtained from the coefficient of determination (R Square) of 0.310, it means that there is an influence of brand ambassadors on brand awareness of 31%. After that, the researcher conducted a simple linear regression analysis study which obtained a constant number of 8,891, a calculated T value of 6,642 > T table (1,660) and a significant value of 0.00 <0.05, so that it could be concluded that H0 was rejected and H1 that is accepted to have influence between variable x (brand ambassador) on variable y brand awareness. Penelitian ini dilakukan untuk mengetahui pengaruh brand ambassador Shani Amelia terhadap brand awareness Yuba Tea. Penelitian dilakukan memakai pendekatan kuantitatif dengan metode penelitian survei. Guna mendapat hasil penelitian, peneliti melakukan cara lewat penyebaran kuesioner ke 100 responden memakai rumus Slovin serta teknik pengambilan datan menggunakan teknik purposive atau judgmental sampling. Populasi didapatkan dari followers Instagram Yuba Tea yang berjumlah 49.300, sedangkan sampel yang digunakan memiliki kriteria yaitu responden yang mengetahui Shani Amelia dan Yuba Tea, berusia 17-34 tahun, jenis kelamin laki-laki dan perempuan, domisili di daerah DKI Jakarta yang tersebar dari Jakarta Barat, Jakarta Selatan, Jakarta Utara, Jakarta Timur, serta Jakarta Pusat. Penelitian ini menggunakan teori brand ambassador dan brand awareness. Teknik pengolahan dan analisis data diperoleh dari koefisien korelasi, koefisien determinasi, uji normalitas, uji parsial (uji t), dan analisis regresi linear sederhana. Didapatkan hasil dari uji korelasi dengan nilai 0,557 hingga bisa diambil kesimpulan variabel brand ambassador dan variabel brand awareness memiliki korelasi sedang, hingga bisa diambil kesimpulan brand ambassador Shani Amelia memberikan pengaruh pada brand awareness Yuba Tea.